Contemporary Shia Tafsir Studies: an Analysis of Muhammad Hādī Ma'rifah's Thought on Nasakh Verse of Beating in Nusyuz - Durrotun Nabilah, Is'ad; Fauzan Zahri, Ahmad (Zawiyah: Jurnal Pemikiran Islam, 2025)
This study discusses Muhammad Hādī Ma'rifah's view on the permission to hit in Surah al-Nisāʾ verse 34 which he believes has undergone a gradual nasakh (abrogation). In the context of nusyuz, one of the solutions mentioned is beating, but with very strict limits so as not to injure and more intended as a symbol of warning, not a form of violence. According to Muhammad Hādī Ma'rifah, this permission to hit has been removed through a gradual approach, along with Islam's emphasis on the value of compassion and respect for women's dignity. The research method used is qualitative with the type of research applied is library research. The main source of literature in this research is the Book of Syubhāt wa Rudūd Hawl al-Qur'ān al-Karīm. The results show that Muhammad Hādī Ma'rifah views the permission to hit in the verse as a transitional policy aimed at slowly eliminating the practice of violence against women. Muhammad Hādī Ma'rifah has three main reasons, namely the interpretation of spanking as a mild, painless action, the strict prohibition in Islamic teachings to hit women, and the emphasis of Islamic teachings on respect for women's dignity. Therefore, taking this verse literally without considering the teachings of the Prophet and the Imams goes against the spirit of the Qur'an which emphasizes compassion, respect, and justice for women.